Self-Control Moralization: The Role of Moral Identity and Moral Foundations in Young Adults - Orellana, Dayanne; Roth, Eric (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
Despite the morality and self-control relationship having been studied in the past, there is still not enough information about how different moral variables, and their possible interaction, affect self-control levels; especially when referring to young adulthood, a critical period for development of self-control and morality. Within the framework of self-control moralization, the current study aimed to explore whether self-control scores were affected by levels of moral identity and binding-individualizing foundations through early adulthood. Data were obtained by an online survey from a non-probabilistic sample (n=626) of young adults from Bolivia. Having found significant correlations between variables, hypotheses were tested employing t-tests and an ANCOVA, with age as a covariate. Findings showed that binding foundations, moral identity, age and the interaction between moral identity and both types of moral foundations had a significant effect on self-control scores and marginal means, with small to moderate effect sizes. Finally, finding’s implications within the theoretical framework of self-control moralization are discussed.